Influence of Omega-3 and Green Tea Extract on Alcohol-Induced Liver Injury in Rats - Hassan Hussein, Ridha; Hassan Ibrahim, Zana (Kurdistan Journal of Applied Research, 2018)
Drinking alcoholic beverages recently is common in many parts of the world, liver is a principal organ that involved in toxic effects of alcohol and it remains a serious health problem globally. Fatty liver (steatosis) was induced in male albino rats by alcohol 40% orally (3.76gm/kgm BW/day) for the period of 4 weeks, then green tea extract (GTE) and omega-3 (OMG-3) fish oil were used as treatments for improvement and investigating their comparison potential role for the next 4 weeks. At the end of the experiment, the rats were fasted overnight, blood samples through the cardiac puncture and liver organ were collected for biochemical and histopathological analysis respectively. Biochemical parameters including: lipid profiles: (total cholesterol (TC), triglycerides (TG), high density lipoprotein-cholesterol (HDL-C) and low density lipoprotein-cholesterol (LDL-C), serum malondialdehyde (MDA), liver function tests (LFT): (Serum albumin (ALB), serum total protein (TP), total serum bilirubin (TSB), serum alkaline phosphatase (ALP), serum alanine aminotransferase (ALT), and serum aspartate aminotransferase (AST) and finally hepatic histological changes were also investigated. Alcoholic rats were associated with significant elevation (P<0.05) in the levels of serum TC, TG, LDL-C, MDA, TSB, ALT, AST and ALP, whereas the levels of serum HDL-C and TP significantly (P<0.05) decreased with no significant change (P>0.05) of serum ALB level. treatment of alcohol-fed rats with GTE and OMG-3 oil either alone or in their combination have significant role (P<0.05) in lowering the injury effects of alcohol evidenced by reversing the results obtained on serum lipid profiles, MDA, LFTs and hepatic histological changes after their treatments during the amelioration study. Ethanol consumption impaired hepatic functions, disturbed lipid metabolism, induced hyperlipidemia and increased oxidative stress. Aqueous extracts of GT and OMG-3 oil significantly improved alcohol-induced liver injury through improvement of serum markers of hepatic injury, their hypolipidemic actions and hepatic histologic recovery. Co-treatments of GT+OMG-3 have more protective effect or faster progression against ALD than their treatments alone.